2010
DOI: 10.1159/000320226
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific IgG and IgA, but Not IgE, Activate the Effector Functions of Eosinophils in the Presence of Antigen

Abstract: Background: Activated eosinophils are thought to play an important role in allergic inflammation. Prior reports suggest that eosinophils have receptors recognizing IgA, IgG and IgE; however, little is known regarding the direct effects of antigens and antigen-specific immunoglobulins on the functions of eosinophils. Methods: To investigate eosinophil activation by antigens mediated by the various antigen-specific immunoglobulins, we used dansyl-conjugated bovine serum albumin (DNS-BSA) and recombinant dansyl-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…These stimuli are known to induce/prime ROS production by eosinophils. [35][36][37] Prior studies demonstrated that cytokine-primed human eosinophils, in response to certain agonists such as lipopolysaccharide, C5a, and CCL11, can rapidly (within seconds) and noncytolytically release not nuclear, but mitochondrial DNA to form extracellular DNA nets. 21 Our findings identify another means by which eosinophils can form DNA nets, more akin temporally and mechanistically to ETosis in neutrophils 16 and mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…These stimuli are known to induce/prime ROS production by eosinophils. [35][36][37] Prior studies demonstrated that cytokine-primed human eosinophils, in response to certain agonists such as lipopolysaccharide, C5a, and CCL11, can rapidly (within seconds) and noncytolytically release not nuclear, but mitochondrial DNA to form extracellular DNA nets. 21 Our findings identify another means by which eosinophils can form DNA nets, more akin temporally and mechanistically to ETosis in neutrophils 16 and mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, their presence as resident immune cells has been largely overlooked, and their physiological functions in disease pathogenesis remain enigmatic. Direct engagement of antigen by eosinophils elicits downstream effector functions including activation, degranulation, release of reactive oxygen species, and antigen presentation (18-21, 25). It had been unknown whether the large population of native eosinophils resident within the small intestine and separated by an epithelial layer from oral antigens entering the lumen might encounter antigen in vivo ,.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils can pinocytose, process and present free antigens to naïve and activated CD4 + T cells (thereby functioning as antigen presenting cells (18-20)). In addition, in vitro eosinophils exposed to antibody:antigen immune complexes exhibit enhanced survival and secretion of granule proteins and reactive oxygen species (21-25). It had not been known whether eosinophils native to the intestinal lamina propria and physically separated from luminal food antigens by a columnar epithelium, might similarly engage soluble food antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the production of ROS by eosinophils can be triggered by the binding of antigen-antibody conjugates on the surface of eosinophils [38]. The inhalation model of fungal asthma reiterates the eosinophilia associated with the clinical allergic asthma which precedes lymphocyte recruitment [7, 9, 10, 12, 17].…”
Section: Discussionmentioning
confidence: 99%